THE EFFECT OF USING SELF-QUESTIONING STRATEGY ON STUDENTS READING COMPREHENSION - Nur Azmi; Sriati Usman (Tadulako University, 2021)
The objective of this research is to find out the effectiveness of using self-questioning strategy on students reading comprehension in the grade eight students at MTs DDI Soni. This research used quasi-experimental design. Research subject were selected using cluster random sampling. The sample of this research was 40 students of the grade eight at MTs DDI Soni. This research used two classes. VIII R.A as experimental class and VIII N.A as control class. The experimental class and control class were given pre-test and post-test, but only the experimental class has given treatment. The mean score of experimental class in pre-test is 34 and post-test is 51,4. While the mean score of control class in pre-test is 37 and post-test is 42,2. Based on the result of the pre-test and post-test, the tcounted of this study is (3,38). In conclusion, the use of self-questioning strategy can improve the reading comprehension at the grade eight studens at MTs DDI Soni.